The role of p53 in myelodysplastic syndromes and acute myeloid leukemia: molecular aspects and clinical implications. Issue 8 (3rd August 2017) - Zhang, Ling; McGraw, Kathy L.; Sallman, David A.; List, Alan F.
Abstract: TP53 gene mutations occurring in patients with myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) are associated with high-risk karyotypes including 17p abnormalities, monosomal and complex cytogenetics. TP53 mutations in these disorders portend rapid disease progression and resistance to conventional therapeutics. Notably, the size of the TP53 mutant clone as measured by mutation allele burden is directly linked to overall survival (OS) confirming the importance of p53 as a negative prognostic variable. In nucleolar stress-induced ribosomopathies, such as del(5q) MDS, disassociation of MDM2 and p53 results in p53 accumulation in erythroid precursors manifested as erythroid hypoplasia. P53 antagonism by lenalidomide or other therapeutics such as antisense oligonucleotides, repopulates erythroid precursors and enhances effective erythropoiesis. These findings demonstrate that p53 is an intriguing therapeutic target that is currently under investigation in MDS and AML. This study reviews molecular advances in understanding the role of p53 in MDS and AML, and explores potential therapeutic strategies in this era of personalized medicine.